MOOC as a complex system - Nakano, Natália [UNESP]; Padua, Mariana Cantisani [UNESP]; Jorente, Maria José Vicentini [UNESP] (Springer Nature, 2017)
Considering the current scenario of technological innovations, re-shaped connections and relationships, discussions on new formats of knowledge construction and dissemination that meet the needs of human beings are taking place. Massive Open Online Courses (MOOCs) are one of these possibilities. MOOCs are open online courses offered on the Internet, often at no costs for the participant, and are viewed by some authors as an instrument for social change once it is claimed to democratize education. Thus, the objective of this paper is to discuss MOOCs as a complex digital environment, specifically from the perspective of Design. We conclude that Design may contribute to the platform both theoretically and in practice, as a good Design allows to reflect and add characteristics of Complexity Theory to the system.
Keywords: Complexity theory; Distributed learning; Information and technology; Instructional design